STRATEGI DAKWAH PIMPINAN DAERAH MUHAMMADIYAH ASAHAN MENGHADAPI TANTANGAN ERA DIGITAL - Br. Sitorus, Dahlia Safutri; Sikumbang, Ahmad Tamrin (Kodifikasia, 2025)
The development of information technology in the digital era has a major impact on various aspects of life, including in the method of delivering da'wah. The Muhammadiyah Regional Leadership (PDM) Asahan as one of the regional level Islamic organizations is required to develop a da'wah strategy that is relevant to the current digital era. This research aims to find out the da'wah strategy of the Muhammadiyah Asahan Regional Leadership in facing the challenges of the digital era. This research is a field research with a descriptive qualitative approach. Data were collected through in-depth interviews and observations. Research sources include the Secretary of PDM Asahan and the Head of the Da'wah Section. Muhammadiyah Asahan Regional Leadership. The results of this study indicate that the Da'wah Strategy of the Muhammadiyah Asahan Regional Leadership in facing the challenges of the digital era runs effectively by utilizing social media and digital platforms as a means of spreading da'wah such as the Official Website, the Blog of the Library and Information Assembly (MPI), and Digital Da'wah Training.